Performance of cotton fabric treated with chitosan-based mordanty as affected by extraction time variations on tannin dyes produced from cocoa husk - Fatwa, Muhammad Iqbal; Firmanto, Hendy; Indarti, Dwi; Piluharto, Bambang; Sulistyo, Yudi Aris; Reza, Muhammad; Ula, Mohammad Munal; Dharmawan, Aditya Dwiki (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
Natural dyes are substances obtained from animals or plants through extraction. The application of synthetic dyes can affect to environmental problems, therefore replace it with natural dyes is become an alternative. Cocoa pod husk still considered as a waste, whereas it is one of source for natural dyes. Cacao pod husk contains flavonoids, tannins, and Î²-carotene compounds which is generate colour. Natural dye is extracted from the husk of the cocoa pod and applied to cotton cloth. Extraction of cocoa husk dyes was carried out with distilled water at 60ËšC with variations of 1, 2, and 3 hours. The resulting extract contains positive tannins but negative Î²-carotene. Variations in the extraction time of natural dyes affect the tannin content extracted. The tannin content extracted with variations of 1, 2, and 3 hours was 18.32; 18.67; and 17.93 ppm. Respectively chitosan-based mordant has a significant effect on the color yield of the fabric. Fabrics with mordant have a darker color than fabrics that are not applied with mordant process. The use of nanochitosan and citric acid crosslinkers can maintain the aging color of the fabric. The FTIR results on the fabric showed that color aging occurred due to the presence of ester groups formed between chitosan and dyes. Chitosan-based mordant coating provides better color than without mordant coating. Fabrics coated with chitosan had the best fastness value of 4 (Good).